PENGEMBANGAN STRATEGI BISNIS MELALUI ANALISIS SWOT DAN BUSSINES MODEL CANVAS: STUDI KASUS PADA UMKM “COFFEE LABORATORIUM” KABUPATEN BADUNG BALI - I MADE GUNA JULIARTA (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
The intense competition in the business world, particularly in the MSMEs sector, forces entrepreneurs to continually innovate and continually evaluate their businesses to ensure they meet customer expectations. This study aims to determine the business model used by the Coffee Laboratorium MSMEs and to analyze the internal and external conditions of this MSMEs. With a qualitative approach, this study was analyzed using two methods: the Business Model Canvas and SWOT Analysis. Based on the research results, the Coffee Laboratorium MSMEs is in the Grow and Build position with an internal score of 3.00 and a score for external factors of 3.14, indicating strong internal business conditions and a supportive external environment.